2008
DOI: 10.1111/j.1471-1842.2008.00767.x
|View full text |Cite
|
Sign up to set email alerts
|

A computer literacy skills profile of pharmacists residing in two counties of England

Abstract: Background : Pharmacy is an information intensive profession and a pharmacist has to be proficient in health care information management. The advance in information technology and the use of computers to access, retrieve and analyse this information is increasingly important. Yet little is known about pharmacists' computer literacy or information technology skills. Objectives : To gain a better understanding of pharmacists' basic computer skills and their ability to use standard software. Methods : Self-admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 3 publications
2
27
0
Order By: Relevance
“…Two possible confounders are level of education and computer literacy. Both variables, education and computer literacy, have been shown to significantly influence Internet access; but not one's effectiveness in using, or taking advantage of, information obtained through Internet access (Thomas & Rutter, 2008;Valero-Aguilera et al, 2012). Since Internet access is not a criterion in the path model, the exclusion of level of education and computer literacy arguably does not invalidate our findings, as Internet access is captured through the variable Internet diffusion.…”
Section: Limitationsmentioning
confidence: 73%
“…Two possible confounders are level of education and computer literacy. Both variables, education and computer literacy, have been shown to significantly influence Internet access; but not one's effectiveness in using, or taking advantage of, information obtained through Internet access (Thomas & Rutter, 2008;Valero-Aguilera et al, 2012). Since Internet access is not a criterion in the path model, the exclusion of level of education and computer literacy arguably does not invalidate our findings, as Internet access is captured through the variable Internet diffusion.…”
Section: Limitationsmentioning
confidence: 73%
“…Autopoiesis (Maturana and Varela, 1980; Maturana, 2002) is a concept that was initially proposed to explain processes that help biological cells maintain self-integrity. It defines an operationally closed system; with internal processes that are dynamic and ever changing to accommodate the changes in the environment and the demands of survival.…”
Section: Understanding In the Wild: Bridging The Psychological And Bimentioning
confidence: 99%
“…In this sense, the previous motor experiences change the way the objects in the environment are perceived. From this perspective cognition is defined as “… the capacity that a living system exhibits of operating in dynamic structural congruence with the medium in which it exists” (Maturana, 2002, p. 26).…”
Section: Understanding In the Wild: Bridging The Psychological And Bimentioning
confidence: 99%
“…It has been suggested that a physician needs to read 17 articles each day to keep up with current medical literature, yet they have limited time to assess the information they receive [10]. Additionally, studies have shown that access to EBM resources is variable [11-16], and even when resources are available, the ability of physicians to locate relevant information and assess its validity appears limited [11,12,17]. …”
Section: Introductionmentioning
confidence: 99%